Some Useful and Unusual Eponymous Cardiac Surgical Techniques Adopted in Chittagong Medical College Hospital - Nazmul Hosain,; Chowdhury, Muhammad Abdul Quaium; Mohammad Fazle Maruf,; Md Anisuzzaman,; Ahsanuddin Mahmud,; Chowdhury, Minhazur Rahman; Barua, Subir (Cardiovascular Journal, 2024)
Background: Innovation is an integral part of cardiac surgery. A number of natural barriers had to be overcome by the cardiac surgery pioneers to establish open heart surgeries in the 1950s. Since then, surgeons are continuously developing and adopting various innovative techniques to ensure safety and efficacy of cardiac surgery. The Department of Cardiac Surgery of Chittagong Medical College Hospital (CMCH) has some unique characteristics as it was developed isolated from the centers of Dhaka. A few interesting methods are in practice here, which worth mentioning for the outside readers. Some of these procedures have been colloquially named in our department often after the visiting surgeon or the team who introduced those here. Methods: The unique and unusual techniques applied in CMCH were sought and discussed. The hospital records, OT operation notes and ICU log books were thoroughly searched for any clue. The local and visiting team members were interviewed for any information. All available data were compiled and analyzed. Results: Six interesting and useful named surgical techniques adopted in CMCH Cardiac Surgery Department were identified. These are: 1. Marine city ASD Closure Technique, 2. Tendolkar’s Maneuver during CPB, 3. Turkish Sling in CABG, 4. Petlar Stitch in VSD closure, 5. Pyongyang Method of LA Closure and 6. NAK-NAKA De-calcification Procedure for valve surgery. The first two were introduced with the help of visiting Indian Professor Anil Tendolkar, whereas the 3rd was introduced by a visiting Turkish team. The 4th technique was adopted from a pediatric cardiac surgeon from Dhaka. The 5th and 6th techniques have long been in practice at NICVD, which were adopted with some modification in our department. Conclusion: The above mentioned six reproducible techniques are unique and useful. Sharing and discussion of these techniques will enable other Bangladeshi surgeons to adopt these useful tips. Cardiovasc j 2024; 16(2): 86-91